Wrong Again—Rejoinder to Annas - Fenton, Elizabeth (Cambridge quarterly of healthcare ethics, 2010)
It is clear from George Annas's response to our arguments that he has misunderstood and misrepresented our positions on several key points. We suspect that this may be due in part to significant differences between our respective agendas and points of view, so we begin this exchange with an exploration of these differences.